Penggunaan Media Video Motion Graphic untuk Meningkatkan Keterampilan Menulis Teks Deskripsi Siswa Kelas VII : The Use of Motion Graphic Video Media to Improve Descriptive Text Writing Skills of Grade VII Students - Ni Kadek Vivit Widya Lestari; Ade Asih Susiari Tantri; Kadek Wirahyuni (Jurnal IKA, 2026)
PTK research intends to: (1) describe the implementation of learning activities using video motion graphic intructional media for teaching descriptive text writing to VII C students at SMP Negeri 4 Sawan, (2) describe the improvement in descriptive text writing skills of class VII C students at SMP Negeri 4 Sawan towards the use of video motion graphic media, (3) describe the response of class VII C students at SMP Negeri 4 Sawan towards the use of video motion graphic media in learning to write descriptive text. The research was carried out across two cycles by employing three methods of gathering data, namely observation, tests and questionnaires. The accumulated data is processed using qualitative descriptive and quantitative descriptive techniques. Research findings indicate that the use of motion graphic video media was successful in improving learners' competence in writing descriptive passages. Students' writing skills through the use of video motion graphic media improve each cycle. Before the action, the students' average score was recorded at 67.59 and improved to73.52 in the first cycle and rose to 82.59 in cycle II. The average score of students' responses regarding  learning also climbed  from 35.22 in the first cycle action to 38 in the second cycle action, which is in the very positive category. These findings prove that the utilization of motion graphic video media is effective in improving descriptive text writing skills